RDA : Resource description & access : strategies for implementation - El-Sherbini, Magda (Chicago : ALA Editions, an imprint of the American Library Association, 2013)
As the Internet emerged as a tool of accessing information, libraries were confronted with the need to examine their tools for description. New electronic and digital resources became increasingly difficult to catalog and classify. This book is a discussion of key issues related to RDA, to help prepare catalogers for its implementation.
From AACR2 to RDA -- Differences between AACR2 and RDA -- RDA implementation strategies -- Functional requirements for bibliographical records -- Identifying manifestations and items -- Identifying works and expressions and the entity responsible for creating them -- RDA toolkit -- Examples of RDA records -- Checklists.
Includes bibliographical references (pages 373-377) and index.
ALCTS Outstanding Publication Award, 2014
Keywords: Resource description & access; Resource description & access